Chronic Hematuria Increases Chronic Kidney Injury and Epithelial–Mesenchymal Transition in 5/6 Nephrectomy Rats - Xiao, Min; Medipally, Ajay K.; Biederman, Laura; Satoskar, Anjali A.; Ivanov, Iouri; Rovin, Brad H.; Brodsky, Sergey V. (Frontiers in Medicine, 2021)
Chronic kidney disease (CKD) is a common outcome of many kidney diseases. Interstitial fibrosis and tubular atrophy (IFTA) is a histologic hallmark of CKD. Hematuria is a common symptom in many human kidney diseases. Free hemoglobin may affect tubular epithelial cells by generating reactive oxygen species (ROS). Epithelial mesenchymal transition (EMT) of the tubular epithelial cells has been shown to play an important role in the IFTA development. The aim of this study was to determine the effects of chronic hematuria on the CKD progression in 5/6 nephrectomy (5/6NE) rat model of CKD. 5/6NE rats were treated with oral warfarin (0.5 mg/kg/day) or vehicle (control). The animals were monitored for 26 weeks, prothrombin time (PT), serum creatinine (SCr), and hematuria were measured weekly. Stainings for iron, trichrome, and EMT (vimentin, E-cadherin, smooth muscle actin) markers were performed on the remnant kidneys. ROS were detected in the kidneys by protein carbonyl assay at the end of the study. Warfarin treatment resulted in a PT increase 1.5-2.5 times from control and increase in hematuria and serum creatinine. Histologically, warfarin-treated animals had more iron-positive tubular epithelial cells and increased IFTA as compared to control (42.9±17% vs 18.3±2.6%). ROS were increased in the kidney in warfarin-treated rats. The number of tubules that show evidence of EMT was significantly higher in warfarin-treated 5/6NE as compared to control 5/6NE rats. Chronic hematuria results in increased iron-positive tubular epithelial cells, EMT, and more prominent IFTA in CKD rats. Our data suggests an important role of chronic hematuria in the progression of CKD.